Teachers' Professional Development and Instructional Quality: A Longitudinal Study on Curriculum Reform Implementation in Primary Schools - Mustamin, Kaso; Hidayati, Andi; Hidayah; Maq, Mumu Muzayyin; Yusuf (Academy of Education Journal, 2025)
This longitudinal qualitative study investigates the relationship between teachers' professional development (TPD) programs and instructional quality during curriculum reform implementation in Indonesian primary schools. Using a phenomenological approach, this research examines how TPD initiatives influence teaching practices and classroom instruction quality over time. The study employed semi-structured interviews with 12 primary school teachers participating in Indonesia's curriculum reform, conducted at three time points over 18 months. Data were analyzed using inductive thematic analysis to identify patterns and themes related to teachers' experiences with professional development and changes in instructional quality. Findings reveal four major themes: (1) transformative learning experiences through collaborative professional development, (2) gradual improvement in pedagogical content knowledge, (3) enhanced student engagement through differentiated instruction, and (4) persistent systemic barriers to full implementation. The study demonstrates that sustained, school-based TPD programs significantly improve instructional quality when supported by adequate resources and administrative leadership. However, teachers faced challenges including limited materials, time constraints, and insufficient follow-up support. The research contributes to understanding how longitudinal TPD approaches can effectively support curriculum reform implementation in developing country contexts. Implications include recommendations for policymakers to design comprehensive, sustained professional development programs that address both technical and systemic implementation challenges.